PENGARUH LATAR BELAKANG PENDIDIKAN DAN PENGETAHUAN TENTANG AKUNTANSI TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI PADA PEDAGANG DI WILAYAH KELURAHAN HELVETIA TENGAH MEDAN - Saut Djosua Henrianto Sitorus (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
Accounting information is very helpful in taking a decision. But many entrepreneurs who have no knowledge of accounting and among them there are yet to understand the importance of record keeping and bookkeeping for business continuity. The purpose of this research is to know the influence of educational background and knowledge of the accounting of the use of accounting information systems. This type of research is a research associate. The population was the entire existing traders in the village Central Medan Helvetia as many as 49 people. The research sample is the total population that is 49 respondents. Methods of analysis used in this study was the quantitative methods of analysis. The data were analyzed by multiple regression test. The research results obtained that the educational background and the p value = 0.004 and variable knowledge of accounting with p value = 0.001 which means each free variable effect on variables are bound.